Low-temperature nodular cast iron, preparation method and QT400-18L volute casting

By using specific pretreatment agents and incubators in spheroidized incubation treatment, the content of Si, Mn and V and the reaction sequence is controlled, the problem of insufficient tensile strength and impact absorption energy of low-temperature ductile iron is solved, and the preparation of high-performance low-temperature ductile iron is achieved.

CN120138494AActive Publication Date: 2025-06-13GUANGDONG ZHONGTIAN CHUANGZHAN DUCTILE IRON CO LTD

Patent Information

Application Number
CN202510349015.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-06-13
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

The existing low-temperature ductile iron has insufficient tensile strength and impact absorption energy at low temperatures, making it difficult to meet the needs of volute castings and other fields.

Method used

By using pretreatment agent A and special inoculant B during the spheroidization treatment, the content of Si, Mn and V is adjusted, and combined with the reaction sequence control in the spheroidization treatment, low-temperature ductile iron with excellent mechanical properties is prepared.

Benefits of technology

It significantly improves the tensile strength, elongation after break and energy absorption of low-temperature impact of low-temperature ductile iron, meeting the high-performance needs in fields such as volute castings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120138494A_ABST
    Figure CN120138494A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of nodular cast iron, and discloses low-temperature nodular cast iron, a preparation method and a QT400-18L volute casting. The low-temperature nodular cast iron and the nodular cast iron are obtained through spheroidizing inoculation treatment of a pretreating agent A and a special-effect inoculant B; the pretreating agent A comprises the following components in percentage by weight: 45-50% of Si, 1.0-1.5% of Ca, 9-10% of Ba, 0.8-0.9% of La, 0.8-1.0% of Al, less than or equal to 0.005% of Ti and the balance of Fe, and the granularity of the pretreating agent A is 2-5mm; the special-effect inoculant B comprises the following components in percentage by weight: 58-62% of Si, 0.8-1.0% of Ca, 1.9-2.0% of Bi, 1.0-1.2% of Al, less than or equal to 0.005% of Ti and the balance of Fe, and the granularity of the special-effect inoculant B is 3-8mm; the nodular cast iron comprises the following components in percentage by weight: 3.72 to 3.78 percent of C, 2.40 to 2.50 percent of Si, 0.09 to 0.12 percent of Mn, less than or equal to 0.015 percent of P, 0.005 to 0.010 percent of S, less than or equal to 0.008 percent of Ti, 0.0035 to 0.005 percent of Sb, 0.05 to 0.08 percent of V, 0.008 to 0.010 percent of La, 0.040 to 0.050 percent of Mg and the balance of Fe. According to the low-temperature nodular cast iron, the nodular cast iron with high-low-temperature tensile strength, high percentage elongation after fracture and high-low-temperature impact energy absorption is effectively obtained through comprehensive adjustment of the Si content, the Mn content and the V content in combination with addition of the pretreating agent A and the special-effect inoculant B in nodulizing inoculation treatment under the specific chemical components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of ductile iron, and more specifically, relates to a low-temperature ductile iron, a preparation method and a QT400-18L volute casting. Background Art

[0002] In the solidification process of ductile iron, a special type of cast iron, carbon precipitates in the form of spherical graphite. This characteristic makes it significantly different from gray iron in the metallographic structure, eliminating the cutting effect of sharp graphite in gray iron on the metal matrix, thus significantly reducing the stress concentration phenomenon; this enables the strength utilization rate of the metal matrix to reach 70-90%, fully demonstrating its superior mechanical properties.

[0003] With the continuous growth of the output and the continuous improvement of the performance of ductile iron, it has gradually occupied a place in the field of metal structural materials, even partially replacing forged steel and cast steel, becoming a metal material with great development potential. Therefore, in-depth research on the metallographic structure and mechanical properties of ductile iron is undoubtedly the key to making full use of its excellent performance and promoting its wide application.

[0004] Ordinary ductile iron is prone to brittle fracture below -40°C, restricting its application in the fields of engineering machinery, maglev track beams, fan castings, etc. in extremely cold regions; based on this, Western developed countries took the lead in formulating the EN-GJS series of low-temperature ductile iron standards (such as the impact absorption energy at -40°C ≥ 12J).

[0005] The application fields of low-temperature ductile iron are very extensive; in the field of mechanical engineering, it is often used to manufacture components that require high strength and wear resistance, such as gears, cycloidal pinwheels, and cylinder blocks of diesel engines. In the field of automobile manufacturing, low-temperature ductile iron is often used to manufacture key components such as cylinder blocks and crankcases of engines. In the field of aerospace, it is also widely used to manufacture key components such as rotors, turbine blades, and combustion chambers of aircraft engines.

[0006] Traditional methods for improving the low-temperature impact absorption energy are: (1) through graphitizing annealing heat treatment; (2) adding nickel or other metal elements.

[0007] As in the prior art 1: Chinese Patent Application No. 202411325746.X discloses a low-temperature ductile iron and its preparation method and application. The CEL of the low-temperature ductile iron is 4.25 - 4.3, and the mass percentages of the chemical components are C: 3.4% - 4.0%, Si: 1.8% - 2.3%, Mn ≤ 0.2%, S ≤ 0.02%, P ≤ 0.03%, Ni: 1.2% - 1.6%, and the balance is Fe. Its preparation method includes steps such as selecting raw materials, batching, melting, spheroidizing inoculation, and casting. In the as-cast state of the low-temperature ductile iron of the present invention, at normal temperature and as low as -40°C, the tensile strength σb ≥ 450 MPa, the elongation at break ≥ 10%, and the average impact absorption energy AKV of the V-notch specimen ≥ 10 J.

[0008] The prior art 1 can prepare low-temperature ductile iron with a tensile strength σb ≥ 450 MPa. Its specification states: "Nickel is a graphitizing element, and nickel strengthening ferrite can improve the strength and impact toughness of ductile iron", indicating that the prior art 1 enables the low-temperature ductile iron to be applied to the production of pads for railway rail transit in cold regions through adding nickel element, which is a good technology; however, due to the excessive nickel content, it seriously affects the elongation at break of the ductile iron. When it is applied to the production of volute castings in other fields such as fans, compressors, and centrifugal pumps, there will be a problem, that is, the elongation at break and the average impact absorption energy of this low-temperature ductile iron are not high enough to meet the requirements of volute castings. Summary of the Invention

[0009] The main object of the present invention is to provide a low-temperature ductile iron that still has excellent mechanical properties even at low temperatures, not only has a high tensile strength, but also has good performance in the elongation at break and the impact absorption energy of V-notch specimens at -40°C and -60°C, and can fully meet the product requirements.

[0010] Another object of the present invention is to provide a preparation method of low-temperature ductile iron. The low-temperature ductile iron prepared by this method can effectively ensure the quality of ductile iron and has relatively excellent mechanical properties.

[0011] Another object of the present invention is to provide a QT400-18L volute casting, which has a high tensile strength, elongation at break, and impact absorption energy of V-notch specimens at -40°C and -60°C, and can fully meet the requirements.

[0012] To achieve the above object, the present invention provides a ductile iron at low temperature. The ductile iron is obtained by spheroidizing and inoculating treatment with a pretreatment agent A and a special inoculant B. The composition of the pretreatment agent A is: Si: 45 - 50%, Ca: 1.0 - 1.5%, Ba: 9 - 10%, La: 0.8 - 0.9%, Al: 0.8 - 1.0%, Ti ≤ 0.005%, the balance is Fe, and the particle size is 2 - 5 mm; the composition of the special inoculant B is: Si: 58 - 62%, Ca: 0.8 - 1.0%, Bi: 1.9 - 2.0%, Al: 1.0 - 1.2%, Ti ≤ 0.005%, the balance is Fe, and the particle size is 3 - 8 mm;

[0013] The weight percentage composition of the ductile iron is: C: 3.72 - 3.78%, Si: 2.40 - 2.50%, Mn: 0.09 - 0.12%, P ≤ 0.015%, S: 0.005 - 0.010%, Ti ≤ 0.008%, Sb: 0.0035 - 0.005%, V: 0.05 - 0.08%, La: 0.008 - 0.010%, Mg: 0.040 - 0.050%, the balance is Fe.

[0014] The prior art generally improves the impact energy absorption of the V-notch specimen of ductile iron at low temperature by adopting graphitizing annealing heat treatment or adding elements such as nickel. However, during graphitizing annealing heat treatment, especially for large castings (heavy weight or large external dimensions), large annealing is required. Affected by the temperature control stability of the equipment, uneven quantity and distribution of ferrite will occur after annealing, thus restricting the mechanical properties of ductile iron. It is difficult to balance the elongation rate and the average impact energy absorption of ductile iron at low temperature by adding nickel. The above two prior arts greatly increase the cost.

[0015] Through the limitation of the composition of the ductile iron at low temperature and the selection of the pretreatment agent A and the special inoculant B during the spheroidizing and inoculating treatment process, the present invention can effectively improve the elongation after fracture and the impact energy absorption of the ductile iron at low temperature, and the obtained ductile iron at low temperature has good tensile strength.

[0016] The present invention also discloses a preparation method of ductile iron at low temperature, including the following steps:

[0017] Step 1: Taking the total mass of high-purity pig iron and high-purity scrap steel as 100%, by mass percentage, 30 - 40% high-purity pig iron, 60 - 70% high-purity scrap steel, 2.26 - 2.82% low-sulfur and low-nitrogen carburizer, 1.86 - 2.23% ferrosilicon, and 0.07 - 0.11% ferrovanadium are added into an electric furnace to melt into molten iron, and the tapping temperature is controlled at 1460 - 1470 °C;

[0018] Step 2: Place the spheroidizing agent, pretreatment agent A, and special-effect inoculant B in the ladle, with pretreatment agent A and special-effect inoculant B on both sides of the ladle respectively. Then cover with antimony pellets and steel chips, and pour the molten iron into the ladle on the side of pretreatment agent A for spheroidizing inoculation treatment; the addition amount of pretreatment agent A is 0.4% of the weight of the molten iron, and the addition amount of special-effect inoculant B is 0.3% of the weight of the molten iron.

[0019] Step 3: Pour the molten iron, and add special-effect inoculant C for in-stream inoculation treatment during pouring.

[0020] Preferably, the addition amount of the spheroidizing agent in Step 2 is 1% of the weight of the molten iron, and the composition is: Mg: 5.5 - 6.0%, Si: 43 - 48%, Ca: 1.9 - 2.1%, La: 1.0 - 1.5%, Al: 0.5 - 0.6%, Ti ≤ 0.005%, the balance is Fe, and the particle size is 5 - 20 mm.

[0021] Preferably, the particle sizes of the antimony pellets and steel chips in Step 2 are both 0.7 - 2 mm, the addition amount of the antimony pellets is 0.0040 - 0.0056% of the weight of the molten iron, and the addition amount of the steel chips is 1.5 - 2.0% of the weight of the molten iron.

[0022] Preferably, the addition amount of special-effect inoculant C is 0.2% of the weight of the molten iron, and the composition is: Si: 70 - 72%, Ca: 1.5 - 1.7%, S + O: 0.8 - 0.9%, Al: 0.6 - 0.7%, Ti ≤ 0.005%, the balance is Fe, and the particle size is 0.2 - 0.7 mm.

[0023] Preferably, the molten iron obtained in Step 1 has the following weight percentages of components: C: 3.72 - 3.78%, Si: 1.47 - 1.65%, Mn: 0.09 - 0.12%, P ≤ 0.015%, S: 0.010 - 0.015%, Ti ≤ 0.008%, V: 0.05 - 0.08%, the balance is Fe.

[0024] The present invention also discloses a QT400 - 18L volute casting, which is obtained by casting with the above-mentioned low-temperature ductile iron.

[0025] Beneficial effects

[0026] Compared with the prior art, the present invention has at least the following advantages:

[0027] (1) The present invention discloses a low-temperature ductile iron. Under a specific chemical composition, the low-temperature tensile strength is improved by adjusting the Si content, and the low-temperature impact energy absorption is improved by adjusting the V content.

[0028] (2) The ductile iron of the present invention, under specific chemical compositions, through the comprehensive adjustment of the Si content, Mn content and V content, combined with the addition of the pretreatment agent A and the special inoculant B in the spheroidizing inoculation treatment, effectively obtains ductile iron with high and low temperature tensile strengths, high elongation after fracture and high and low temperature impact absorption energies;

[0029] (3) The present invention discloses a preparation method of low-temperature ductile iron. By pouring molten iron into the ladle towards the side of the pretreatment agent A during the spheroidizing inoculation treatment, the reaction sequence of the pretreatment agent A and the special inoculant B is controlled, and the simultaneous reaction of the pretreatment agent A and the special inoculant B with molten iron is avoided, effectively exerting the synergistic cooperation of the trace alloy contents in the pretreatment agent and the special inoculant, and preparing ductile iron with high and low temperature tensile strengths, high elongation after fracture and high and low temperature impact absorption energies. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The present invention will be further described below in conjunction with the drawings and embodiments;

[0031] Figure 1 is a schematic diagram of the placement of the pretreatment agent, special inoculant, spheroidizing agent, etc. in the ladle of the present invention;

[0032] Figure 2 is the spheroidization rate (100 times before corrosion) of the test block cast in Example 2;

[0033] Figure 3 is the matrix structure (100 times after corrosion) of the test block cast in Example 2;

[0034] Figure 4 is a three-dimensional view of the volute casting of the present invention of QT400-18L.

[0035] Figure 1 In, 1 is the dam of the ladle; 2 is the pretreatment agent A; 3 is the spheroidizing agent; 4 is the special inoculant B; 5 is the mixture of antimony grains and broken steel grains. DETAILED DESCRIPTION OF THE EMBODIMENTS

[0036] The present invention will be further described below in conjunction with the embodiments, but it does not constitute any limitation to the present invention. Any limited modifications made within the scope of the claims of the present invention are still within the scope of the claims of the present invention.

[0037] In order to illustrate the technical content of the present invention in detail, the following further description is made in conjunction with the embodiments.

[0038] In the following examples and comparative examples, the composition of the spheroidizing agent is: Mg: 5.7%, Si: 44%, Ca: 2%, La: 1.0%, Al: 0.53%, Ti: 0.005%, the balance is Fe, particle size: 5-20 mm;

[0039] The composition of the pretreatment agent A is: Si: 46%, Ca: 1.3%, Ba: 9%, La: 0.8%, Al: 1.0%, Ti: 0.003%, the balance is Fe, particle size: 2 - 5 mm;

[0040] The composition of the special inoculant B is: Si: 61%, Ca: 0.8%, Bi: 2.0%, Al: 1.2%, Ti: 0.004%, the balance is Fe, particle size: 3 - 8 mm;

[0041] The composition of the special inoculant C is: Si: 72%, Ca: 1.6%, S + O: 0.8%, Al: 0.7%, Ti: 0.005%, the balance is Fe, particle size: 0.2 - 0.7 mm;

[0042] The composition of the pretreatment agent D is: Si: 47%, Ca: 1.5%, Ba: 10%, Al: 0.8%, the balance is Fe, particle size: 2 - 5 mm;

[0043] The composition of the special inoculant E is: Si: 60%, Ca: 1.1%, Al: 1.2%, the balance is Fe, particle size: 3 - 8 mm;

[0044] The composition of the high - purity pig iron is: C: 4.2%, Si: 0.5%, Mn: 0.05%, P: 0.012%, S: 0.010%, Ti: 0.005%, the balance is Fe + other trace elements;

[0045] The composition of the high - purity scrap steel is: C: 0.05%, Si: 0.11%, Mn: 0.12%, P: 0.010%, S: 0.009%, Ti: 0.006%, the balance is Fe + other trace elements;

[0046] The composition of the low - sulfur and low - nitrogen recarburizer is: C: 99.8%, S: 0.003%, N: 150 ppm, the balance is ash, absorption rate: 90%;

[0047] The composition of the ferrosilicon is: Si: 70%, Al: 0.12%, the balance is Fe;

[0048] The main composition of the antimony granules is: Sb: 99.9%, absorption rate: 90%;

[0049] The main composition of the ferrovanadium is: V: 81%, absorption rate: 90%.

[0050] The absorption rate of the Si element in the above raw materials (except high - purity pig iron and high - purity scrap steel) is 90%.

[0051] In the following examples and comparative examples, the particle sizes of the antimony granules and the broken steel granules are both 0.7 - 2 mm.

[0052] In the following examples and comparative examples, unless otherwise specified, the % is the weight percentage.

[0053] In the following examples and comparative examples, the ladle used Figure 1 is provided with a dam 1 in the middle to separate the pretreatment agent A (or D) and the special inoculant B (or E).

[0054] Example 1

[0055] Step 1: Taking the total mass of high-purity pig iron and high-purity scrap steel as 100%, 34% high-purity pig iron, 66% high-purity scrap steel, 2.58% low-sulfur and low-nitrogen carburizer, 2.08% ferrosilicon, and 0.08% ferrovanadium are added as raw materials into the electric furnace to melt into molten iron, and the tapping temperature is controlled at 1465 °C;

[0056] Sampling and testing are carried out to adjust the molten iron composition to the following weight percentages: C: 3.78%, Si: 1.55%, Mn: 0.10%, P: 0.013%, S: 0.012%, Ti: 0.008%, V: 0.058%, the balance is Fe;

[0057] Step 2: Place 1% of the molten iron weight of the spheroidizing agent, 0.4% of the molten iron weight of the pretreatment agent A, and 0.3% of the molten iron weight of the special inoculant B in the ladle, and the pretreatment agent A and the special inoculant B are on both sides of the ladle respectively. Then cover 0.0040% of the molten iron weight of antimony grains and 1.7% of the molten iron weight of steel chips, and pour the molten iron into the ladle on the side of the pretreatment agent A for spheroidizing inoculation treatment;

[0058] Step 3: Pour the molten iron, and add 0.2% of the molten iron weight of the special inoculant C for in-stream inoculation treatment during pouring;

[0059] The sampled and analyzed composition of the finally obtained ductile iron is as follows: C: 3.78%, Si: 2.40%, Mn: 0.10%, P: 0.013%, S: 0.008%, Ti: 0.008%, Sb: 0.0035%, V: 0.058%, La: 0.009%, Mg: 0.046%, the balance is Fe.

[0060] Example 2

[0061] Step 1: Taking the total mass of high-purity pig iron and high-purity scrap steel as 100%, 30% high-purity pig iron, 70% high-purity scrap steel, 2.75% low-sulfur and low-nitrogen carburizer, 2.06% ferrosilicon, and 0.11% ferrovanadium are added as raw materials into the electric furnace to melt into molten iron, and the tapping temperature is controlled at 1465 °C;

[0062] Sample and test the molten iron composition and adjust it to the following weight percentages: C: 3.77%, Si: 1.60%, Mn: 0.099%, P: 0.010%, S: 0.011%, Ti: 0.005%, V: 0.08%, balance Fe;

[0063] Step 2: Place a spheroidizing agent of 1% of the molten iron weight, a pretreatment agent A of 0.4% of the molten iron weight, and a special inoculant B of 0.3% of the molten iron weight in the ladle, with the pretreatment agent A and the special inoculant B on both sides of the ladle respectively. Then cover with antimony grains of 0.0048% of the molten iron weight and broken steel grains of 1.5% of the molten iron weight. Pour the molten iron into the ladle from the side of the pretreatment agent A for spheroidizing inoculation treatment;

[0064] Step 3: Pour the molten iron, and add a special inoculant C of 0.2% of the molten iron weight for in-stream inoculation treatment during pouring;

[0065] The sampled and analyzed composition of the finally obtained ductile iron is as follows: C: 3.76%, Si: 2.45%, Mn: 0.099%, P: 0.010%, S: 0.007%, Ti: 0.005%, Sb: 0.0043%, V: 0.08%, La: 0.010%, Mg: 0.043%, balance Fe.

[0066] Example 3

[0067] Step 1: Taking the total mass of high-purity pig iron and high-purity scrap steel as 100%, add 40% high-purity pig iron, 60% high-purity scrap steel, 2.26% low-sulfur and low-nitrogen carburizer, 2.18% ferrosilicon, and 0.1% ferrovanadium as raw materials into the electric furnace to melt into molten iron, and control the tapping temperature to be 1465°C;

[0068] Sample and test the molten iron composition and adjust it to the following weight percentages: C: 3.73%, Si: 1.64%, Mn: 0.092%, P: 0.015%, S: 0.008%, Ti: 0.006%, V: 0.073%, balance Fe;

[0069] Step 2: Place a spheroidizing agent of 1% of the molten iron weight, a pretreatment agent A of 0.4% of the molten iron weight, and a special inoculant B of 0.3% of the molten iron weight in the ladle, with the pretreatment agent A and the special inoculant B on both sides of the ladle respectively. Then cover with antimony grains of 0.0056% of the molten iron weight and broken steel grains of 2% of the molten iron weight. Pour the molten iron into the ladle from the side of the pretreatment agent A for spheroidizing inoculation treatment;

[0070] Step 3: Pour the molten iron, and add a special inoculant C of 0.2% of the molten iron weight for in-stream inoculation treatment during pouring;

[0071] The components of the finally obtained ductile iron by sampling and analysis are as follows: C: 3.72%, Si: 2.49%, Mn: 0.0092%, P: 0.015%, S: 0.007%, Ti: 0.006%, Sb: 0.0050%, V: 0.073%, La: 0.010%, Mg: 0.0448%, the balance is Fe.

[0072] Comparative Example 1

[0073] It is generally the same as Example 2, except that the pretreatment agent A is replaced by pretreatment agent D.

[0074] Comparative Example 2

[0075] It is generally the same as Example 2, except that the special inoculant B is replaced by special inoculant E.

[0076] Comparative Example 3

[0077] It is generally the same as Example 2, except that in Step 2, the pretreatment agent A and the special inoculant B are on the same side of the ladle.

[0078] Comparative Example 4

[0079] It is generally the same as Example 2, except that Step 2 is changed to: Place 1% of the weight of the molten iron of the spheroidizing agent, 0.4% of the weight of the molten iron of the pretreatment agent A, and 0.3% of the weight of the molten iron of the special inoculant B in the ladle, and the pretreatment agent A and the special inoculant B are on both sides of the ladle respectively, then cover with 0.0048% of the weight of the molten iron of antimony pellets and 1.5% of crushed steel pellets, and pour the molten iron into the ladle on the side of the special inoculant B for spheroidizing inoculation treatment.

[0080] Comparative Example 5

[0081] It is generally the same as Example 2, except that in Step 1, the molten iron composition is sampled and detected and adjusted to the following weight percentages: C: 3.77%, Si: 1.25%, Mn: 0.099%, P: 0.010%, S: 0.011%, Ti: 0.005%, V: 0.08%, the balance is Fe;

[0082] The components of the finally obtained ductile iron by sampling and analysis are as follows: C: 3.77%, Si: 2.10%, Mn: 0.0099%, P: 0.010%, S: 0.005%, Ti: 0.005%, Sb: 0.0043%, V: 0.08%, La: 0.009%, Mg: 0.042%, the balance is Fe.

[0083] Comparative Example 6

[0084] Substantially the same as Example 2, except that in step 1, the molten iron composition is sampled, detected and adjusted to the following weight percentages: C: 3.77%, Si: 1.60%, Mn: 0.099%, P: 0.010%, S: 0.011%, Ti: 0.005%, V: 0.04%, the balance being Fe;

[0085] The components of the nodular cast iron finally obtained are sampled and analyzed as follows: C: 3.76%, Si: 2.45%, Mn: 0.099%, P: 0.010%, S: 0.007%, Ti: 0.005%, Sb: 0.0043%, V: 0.04%, La: 0.010%, Mg: 0.044%, the balance being Fe.

[0086] Comparative Example 7

[0087] Substantially the same as Example 2, except that in step 1, the molten iron composition is sampled, detected and adjusted to the following weight percentages: C: 3.77%, Si: 1.60%, Mn: 0.099%, P: 0.010%, S: 0.011%, Ti: 0.005%, V: 0.09%, the balance being Fe;

[0088] The components of the nodular cast iron finally obtained are sampled and analyzed as follows: C: 3.76%, Si: 2.45%, Mn: 0.099%, P: 0.010%, S: 0.007%, Ti: 0.005%, Sb: 0.0043%, V: 0.09%, La: 0.010%, Mg: 0.045%, the balance being Fe.

[0089] Test results

[0090] I. Composition

[0091] The content of each element in the above examples and comparative examples is detected and analyzed by a spectrometer.

[0092] II. Mechanical properties

[0093] The nodular cast iron obtained in the above examples and comparative examples is all cast into test blocks with dimensions of 400 mm × 400 mm × 400 mm.

[0094] Samples are taken from the center positions of the test blocks obtained in Examples 1-3 and Comparative Examples 1-6, and mechanical property tests are carried out in accordance with the provisions of GB / T 1348-2019 "Nodular Cast Iron Parts". The impact absorption energy of the V-notch specimens at -40 °C and -60 °C is the average value of the results of 3 impact specimens. The results are shown in Table 1;

[0095] Table 1 Test results of mechanical properties of nodular cast iron

[0096]

[0097] It can be seen from the results in Table 1 that:

[0098] It can be known from the data of Examples 1-3 that the present invention can obtain ductile iron with high tensile strength, high elongation after fracture and high average low-temperature impact energy absorption, and is significantly higher than the requirements of the performance indicators corresponding to Grade QT400-18L and casting wall thickness 60 < t ≤ 200 mm in Tables 1 and 2 of GB / T 1348-2019 "Ductile Iron Castings". Therefore, the obtained ductile iron has very excellent comprehensive mechanical properties;

[0099] And it should be noted that according to the general knowledge in the art, it is considered that the best tensile strength, elongation after fracture and low-temperature impact energy absorption can be obtained when the silicon content of ductile iron is between 2.1-2.4%; however, the present invention discovers that through the selection of the pretreatment agent and the special inoculant during the spheroidizing inoculation process, effectively exerting the synergistic cooperation of the trace alloy content in the pretreatment agent and the special inoculant, and then cooperating with the control of the silicon content, the mechanical properties of ductile iron can be effectively improved. While maintaining a high tensile strength, the elongation after fracture and the low-temperature impact energy absorption have both been effectively improved.

[0100] It can be known from the data comparison between Example 2 and Comparative Example 1 that the composition of the pretreatment agent will seriously affect the tensile strength of ductile iron, and it also has a certain influence on the elongation after fracture and the low-temperature impact energy absorption of ductile iron; it is speculated that the reason is that during the pretreatment reaction of spheroidizing inoculation, the La element in the pretreatment agent of Example 2 will affect the quality of the alloy reaction, thereby affecting the graphite morphology, matrix structure, etc.; however, Comparative Example 1 does not have the La element, so the alloy quality is not well improved during the reaction of the molten iron with the pretreatment agent, and therefore the mechanical properties shown are significantly weaker than those of Example 2.

[0101] It can be known from the data comparison between Example 2 and Comparative Example 2 that the selection of the special inoculant in the spheroidizing inoculation treatment will seriously affect the elongation rate and the average low-temperature impact energy absorption of ductile iron. Comparative Example 2 of the present invention uses a special inoculant without Bi element, which may seriously affect the distribution morphology of ferrite during the spheroidizing inoculation reaction process, so that the ductile iron conforms to the general knowledge in the art that further increase in the silicon content of ductile iron will lead to a significant decrease in the elongation after fracture and the low-temperature impact energy absorption of ductile iron after exceeding 2.4%.

[0102] According to the data comparison of Example 2 and Comparative Example 3 and Comparative Example 4, it can be seen that in the production process of ductile iron of the present invention, the reaction sequence of nodulizing and inoculating molten iron with pretreatment agent A and special inoculant B will have a serious impact on the mechanical properties of ductile iron; by controlling the selection of pretreatment agent and special inoculant and the reaction sequence during the nodulizing and inoculating reaction process, and then matching with the component composition of ductile iron, the present invention can effectively improve the comprehensive mechanical properties of ductile iron, especially the elongation after fracture and the low-temperature impact energy absorption of ductile iron have been significantly improved.

[0103] According to the data comparison of Example 2 and Comparative Example 5, it can be seen that if the silicon content of ductile iron is too low, it will cause a significant decrease in the tensile strength and elongation after fracture of ductile iron, and there is also a relatively obvious decrease in the low-temperature impact energy absorption;

[0104] According to the data comparison of Example 2 and Comparative Example 6 and Comparative Example 7, it can be seen that if the V content of ductile iron is too low, although it will not have an obvious impact on the tensile strength of ductile iron, it will seriously affect the low-temperature impact energy absorption of ductile iron and will also have a certain impact on the elongation after fracture; if the V content of ductile iron is too high, the tensile strength, elongation after fracture and low-temperature impact energy absorption of ductile iron will all decrease significantly, resulting in poor mechanical properties;

[0105] It shows that the improvement of the mechanical properties of ductile iron in the present invention requires the combination and coordination of three points: (1) it is necessary to control the component composition of ductile iron; (2) it is necessary to control the composition of the pretreatment agent and special inoculant during the nodulizing and inoculating treatment process of ductile iron; (3) during the nodulizing and inoculating treatment process, the reaction sequence of molten iron with the pretreatment agent and special inoculant needs to be strictly controlled; only with the synchronous coordination of the three can ductile iron with excellent properties such as tensile strength, elongation rate and low-temperature impact energy absorption be obtained.

[0106] III. Metallographic structure inspection

[0107] The test block obtained by casting Example 2 was subjected to corrosion treatment, and the center point was taken before and after corrosion for metallographic microscope detection and analysis of its metallographic structure. The results are as Figure 2 and Figure 3 shown;

[0108] Figure 2 is the metallographic structure diagram before the corrosion of the test block. It can be seen that the nodularity is 95%;

[0109] Figure 3 is the metallographic structure diagram after the corrosion of the test block. It can be analyzed that the pearlite content is 0% and the ferrite content is 100%.

[0110] Application example

[0111] The ductile iron of Example 2 was cast into a furan resin sand mold to obtain a volute casting as Figure 4 . The grade of the casting is QT400-18L, the weight of the casting is 16,300 kg, and the external dimensions of the casting are: 4250 mm × 3820 mm × 1530 mm, with a main wall thickness of 72 mm.

[0112] Composition of the casting: C: 3.75%, Si: 2.46%, Mn: 0.09%, P: 0.011%, S: 0.006%, Ti: 0.005%, Sb: 0.0044%, V: 0.079%, La: 0.009%, Mg: 0.049%, the balance is Fe.

[0113] The mechanical properties of the attached casting test block (type: D) of the casting were inspected. The results were: tensile strength Rm: 485 MPa, yield strength R P0.2 : 318 MPa, elongation after fracture A: 28%, hardness: 161 HBW. Impact absorption energy of -40°C V-notch specimens: 25 J, 23.5 J, 22 J, average value: 23.5 J, impact absorption energy of -60°C V-notch specimens: 20 J, 19 J, 20.5 J, average value: 20 J.

[0114] The volute casting was subjected to a pressure test according to the standard ISO 11484, and the result was that the pressure resistance reached 35 MPa; ultrasonic flaw detection was performed on all positions of the casting, and no defects were found.

[0115] The embodiments presented herein are merely exemplary embodiments selected from all possible combinations of embodiments. The appended claims should not be limited by the embodiments that illustrate the invention. Some of the numerical ranges used in the claims include sub-ranges within them, and variations within these ranges should also be covered by the appended claims.

Claims

1. A low-temperature ductile iron, characterized in that: The ductile iron is obtained by spheroidizing and inoculating with a pretreatment agent A and a special inoculant B; the pretreatment agent A comprises: Si: 45-50%, Ca: 1.0-1.5%, Ba: 9-10%, La: 0.8-0.9%, Al: 0.8-1.0%, Ti≤0.005%, residual Fe, and a particle size of 2-5 mm; the special inoculant B comprises: Si: 58-62%, Ca: 0.8-1.0%, Bi: 1.9-2.0%, Al: 1.0-1.2%, Ti≤0.005%, residual Fe, and a particle size of 3-8 mm; The ductile iron has a weight percentage composition of: C: 3.72-3.78%, Si: 2.40-2.50%, Mn: 0.09-0.12%, P≤0.015%, S: 0.005-0.010%, Ti≤0.008%, Sb: 0.0035-0.005%, V: 0.05-0.08%, La: 0.008-0.010%, Mg: 0.040-0.050%, remainder Fe.

2. A method for preparing low-temperature ductile iron as claimed in claim 1, characterized in that: The steps include: Step 1: Taking the total mass of high-purity pig iron and high-purity scrap steel as 100%, by mass percentage, 30-40% high-purity pig iron, 60-70% high-purity scrap steel, 2.26-2.82% low-sulfur and low-nitrogen carburizer, 1.86-2.23% ferrosilicon, and 0.07-0.11% ferrovanadium are added as raw materials into an electric furnace to be smelted into molten iron, and the outlet water temperature is controlled to be 1460-1470°C; Step 2: placing the spheroidizing agent, pretreatment agent A, and special inoculant B in a ladle, with the pretreatment agent A and the special inoculant B on both sides of the ladle, respectively, and then covering the antimony particles and crushed steel particles, and pouring the molten iron into the ladle toward the side of the pretreatment agent A for spheroidizing and inoculating treatment; the amount of the pretreatment agent A added is 0.4% of the weight of the molten iron, and the amount of the special inoculant B added is 0.3% of the weight of the molten iron; Step 3: pouring molten iron, adding special effect inoculant C for inoculation during pouring.

3. The method for preparing low-temperature ductile iron according to claim 2, characterized in that: The amount of the spheroidizing agent added in step 2 is 1% of the weight of the molten iron, and the composition is: Mg: 5.5-6.0%, Si: 43-48%, Ca: 1.9-2.1%, La: 1.0-1.5%, Al: 0.5-0.6%, Ti≤0.005%, and the remaining Fe, and the particle size is 5-20 mm.

4. The method for preparing low-temperature ductile iron according to claim 2, characterized in that: In step 2, the particle sizes of the antimony particles and the crushed steel particles are both 0.7-2 mm, the amount of antimony particles added is 0.0040-0.0056% of the weight of the molten iron, and the amount of crushed steel particles added is 1.5-2.0% of the weight of the molten iron.

5. The method for preparing low-temperature ductile iron according to claim 2, characterized in that: The added amount of the special inoculant C is 0.2% of the weight of the molten iron, and the composition is: Si: 70-72%, Ca: 1.5-1.7%, S+O: 0.8-0.9%, Al: 0.6-0.7%, Ti≤0.005%, remaining Fe, and the particle size is 0.2-0.7mm.

6. The method for preparing low-temperature ductile iron according to claim 2, characterized in that: The composition of the molten iron obtained in step 1 is as follows by weight percentage: C: 3.72-3.78%, Si: 1.47-1.65%, Mn: 0.09-0.12%, P≤0.015%, S: 0.010-0.015%, Ti≤0.008%, V: 0.05-0.08%, and the remainder is Fe.

7. A QT400-18L volute casting, characterized in that: The low-temperature ductile iron is cast by using the low-temperature ductile iron as claimed in claim 1.

Citation Information

Patent Citations

  • Low-temperature nodular cast iron and preparation method and application thereof

    CN119194224A

  • Nodular cast iron material, composition comprising nodular cast iron, wind power casting and preparation method of wind power casting

    CN107058861A

  • Casting process of nodular iron casting for wind power

    CN112853025A

  • Production process of nodular cast iron with impact toughness at low temperature of-50 DEG

    CN114657307A

  • Super-thick large nodular cast iron and preparation method thereof

    CN116065085A

Cited By

  • Large volute casting and preparation method thereof

    CN120866717A

  • A large volute casting and a method for manufacturing the same

    CN120866717B